Does participation in a multicenter study group affect physician treatment preference? A survey of participants. Issue 6 (November 2020) - Martin, Benjamin D.; Kelly, Derek M.; Nolan, Vikki G.; Matthews, Allison; Flournory, Jolecia; Kim, Harry K.W.
Abstract : Background: Our purpose was to determine if participation in a prospective, multicenter study group will influence surgeons' treatment preferences despite no new evidence reported by the group. Methods: Surveys of treatment preferences in patients with Legg-Calve-Perthes (LCPD) disease and four cases with radiographs were sent to the International Perthes Study Group participants just before the inaugural meeting in 2012 and after the fifth annual meeting in 2016, and results were compared. A treatment change was a move from operative to nonoperative treatment or vice versa, surgeon experience was number of years in practice; the number of annual meetings attended served as a proxy study group participation. Results: Survey responses from 47 surgeons were analyzed. Participation in the study group ranged from one to five meetings, and the average clinical experience was 15 yr. On each survey question, some surgeons changed their response, highlighting changes in treatment preferences over time; however, no association was noted between treatment changes and number of meetings attended or length of surgeon experience. The more meetings attended, the more likely the surgeon used lateral extrusion on radiograph, lateral pillar or Catterall classification, or perfusion MRI as an indication to operate on certain age groups. For one of the four clinical cases, surgeons were 1.8 times more likely to change treatment preference with each meeting attended, and surgeons with less than 15 yr of experience were 8.5 times more likely to change. Conclusions: Although treatment preferences varied, study group participation did not impact decisions for operative versus nonoperative treatment, except in one case. Level of Evidence: Level IV.